Faktor-faktor yang Berhubungan dengan Self-Care Management pada Pasien Penyakit Ginjal Kronik - Nirmala Bakri; Yuliana Syam; Suni Hariati (Journal of Telenursing (JOTING), 2023)
This research aims to summarize the factors related to self-care management in chronic kidney disease (CKD) patients. A literature search was conducted using six databases: Pubmed, Scopus, EBSCOhost, Wiley Online Library, Taylor & Francis, and Garuda. The keywords used were "chronic kidney disease" AND "self-care management" OR "self-care behaviors" OR "self-care practices." The quality of the articles was assessed using the Critical Appraisal Skill Program (CASP) instrument. The search yielded 11 articles included in the review. We identified factors related to self-care management in CKD patients, including individual characteristics, health literacy, self-efficacy, CKD stages, family and peer support, healthcare facility support, and psychological factors. In conclusion, understanding the factors related to self-care management in CKD patients can assist healthcare professionals in comprehending the variables that contribute to CKD patient self-care management from various aspects, leading to improved quality of life, cost savings in treatment, and reduced hospitalization rates. Keywords: Chronic Kidney Disease, Self-Care Behaviors, Self-Care Management, and Self-Care Practices.